PENGGUNAAN SENAM OTAK DALAM MENINGKATKAN KONSENTRASI BELAJAR SISWA SD NEGERI ATEUK ACEH BESAR - Nurrizki Yanti; Syaiful Bahri; Fajriani . (Jurnal Suloh, 2018)
Abstract: Concentration in learning is the most important aspect that must be owned by students in achievement. Without concentration, learning will not work optimally. The purpose of this study was analyzed the influence of brain gymnastics on student learning concentration. To obtain the data, researcher applied a quantitative form of pre-experimental teaching with one group pretest and post test design model. The population of this study was the students of Ateuk Elementary School with consist of class IV, V and VI. The sample was selected by using grid concentration exercise (Harris and Bette L. Harris). The result of this exercise was analyzed by using norms of concentration test scores and obtains 30 students with very low concentrations. The selected sample received 12 sessions of treatment for brain gymnastics. Data analysis using paired sample t-test, and then obtained the result of Sig. value (2-tailed) is 0,000 or probability below 0.05 (0.000 0.05), it means that there is a significant differences between the value of pre-test and post-test students after given treatment of brain gymnastics that is 18,933 3,733. In addition, data analysis also done by using effect size and the result there is a large effect (large effect) on increasing student concentration. The result of hypothesis testing shows that H0 is rejected. Finally, based on these results, researchers recommend to teachers that students to brain exercises before learning process begin in class.Keywords: Brain gymnastics, learning concentration Abstrak: Konsentrasi belajar merupakan aspek terpenting yang harus dimiliki siswa dalam meraih prestasi. Tanpa adanya konsentrasi maka belajar tidak akan berjalan secara optimal. Penelitian ini bertujuan untuk menganalisis pengaruh senam otak terhadap konsentrasi belajar siswa. Pendekatan penelitian yang digunakan yaitu kuantitatif bentuk pre-eksperiment dengan model one group pre-test and post test design. Populasi penelitian adalah seluruh siswa kelas IV, V dan VI di SD Negeri Ateuk Aceh Besar. Penarikan sampel dilakukan dengan tes konsentrasi (grid concentration exercise) oleh Harris and Bette L. Harris. Hasil tes konsentrasi kemudian dianalisis menggunakan norma penilaian tes konsentrasi dan memperoleh 30 siswa dengan konsentrasi sangat rendah dan rendah. Sampel yang dipilih mendapatkan 12 sesi treatment senam otak. Analisis data menggunakan paired sampel t-test, maka diperoleh hasil nilai Sig. (2-tailed) adalah 0,000 atau probabilitas di bawah 0,05 (0,000 0,05). Artinya terdapat perbedaan rata-rata yang signifikan antara nilai pre-test dan nilai post-test siswa setelah diberikan treatment senam otak yaitu 18,9333,733. Selain itu analisis data juga dilakukan dengan menggunakan effect size dan hasilnya terdapat efek yang besar (large effect) terhadap peningkatan konsentrasi siswa. Hasil pengujian hipotesis menunjukkan bahwa Ho ditolak. Berdasarkan hasil tersebut maka peneliti merekomendasikan kepada guru untuk mengintruksikan siswa melakukan senam otak sebelum memulai pelajaran di kelas. Kata kunci: Senam otak, konsentrasi belajar